Splenic Rupture as a Complication of Colonoscopy - Barbeiro,Sandra (2017)
Splenic rupture is a rare but serious complication after colonoscopy, with high global mortality (5%). Diagnosis requires a high index of suspicion because presentation can be subtle, nonspecific, and delayed from hours to days and then not easily attributed to a recent endoscopy. Urgent splenectomy is the most common treatment option. A 73-year-old woman was admitted to the emergency department 8 h following a diagnostic colonoscopy. She presented abdominal pain and syncope. The diagnosis of splenic rupture was made and a splenectomy was urgently performed. The patients postoperative recovery was uneventful. Splenic rupture is a rare complication of colonoscopy which cannot be underestimated in the differential diagnosis of abdominal pain after this procedure. Splenic injuries may occur in apparently uncomplicated, easy colonoscopies performed by experienced endoscopists, with no risk factors identified, as in this case.